2004
DOI: 10.3354/meps269289
|View full text |Cite
|
Sign up to set email alerts
|

Female southern right whales Eubalaena australis: Are there reproductive benefits associated with their coastal distribution off South Africa?

Abstract: Predictability in both meso-and microscale distribution of southern right whale Eubalaena australis females off the coast of South Africa is attributed to maternal philopatry, as well as favourable environmental conditions (calm water, generally shallow sloping, sedimentary sea bed) conducive to reduced energy consumption and a lowered risk of injury for both cows and calves. Spatial differences in reproductive success were compared between favoured (nursery) and nonfavoured (non-nursery) areas and related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 16 publications
2
44
0
Order By: Relevance
“…This female preference has been reported also in southern right whales [80], [81], [82] and humpback whales [83], [84]. In mammals, including baleen whales, there is evidence of strong female site fidelity [13], [85] and resulting in genetic divergence such as in grey whale [14]; elephants [74], ungulates [2] and sea lions [86].…”
Section: Discussionsupporting
confidence: 55%
“…This female preference has been reported also in southern right whales [80], [81], [82] and humpback whales [83], [84]. In mammals, including baleen whales, there is evidence of strong female site fidelity [13], [85] and resulting in genetic divergence such as in grey whale [14]; elephants [74], ungulates [2] and sea lions [86].…”
Section: Discussionsupporting
confidence: 55%
“…Our results indicate that mother-calf social condition is mainly a function of the depth in which the pair moves, which is concordant with the belief that water depth would be a major constraint for the association of mother-calf pairs with others whales since shallow waters limit the movements of courting males within the water column (Smultea 1994, Ersts & Rosenbaum 2003. Avoiding deep waters where the mother-calf pair is easily joined by males would have a positive impact on the offspring survival, as seen in right whales Eubalaena australis off South Africa, where the stranding rate of neonates increased in areas dominated by non-cow individuals (Elwen & Best 2004). The authors suggested this could be caused by inexperienced mothers failing to avoid those sites or their inability to deal with harassment by males.…”
Section: Discussionsupporting
confidence: 69%
“…While avoiding the highest breeding activities and aggression by adult whales in the afternoon could be a plausible explanation for such diurnal movements (see Helweg & Herman 1994, Smultea 1994, Ersts & Rosenbaum 2003, the PCA showed also a positive correlation between time of day and wind speed, which suggests that mother-calf pairs approach the coast more often in afternoon hours off Salinas to avoid rough seas. Coastal protected waters may provide shelter to mother-calf pairs during rough seas helping to save energy (Whitehead & Moore 1982, Elwen & Best 2004. Alternatively, such a difference could be attributed to smaller quieter MC groups that would be harder to see in the rougher waters offshore in the afternoon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sea otters, Riedman et al 1994; polar bears, Atkinson & Ramsay 1995; southern right whales, Elwen & Best 2004). Such a relationship may represent older, more experienced females retaining a higher position in the social hierarchy and thus being exposed to better mating opportunities (Côtè & Festa-Bianchet 2001).…”
Section: Introductionmentioning
confidence: 99%